Application of Ultrasonic Bonding in Leds and Led Lamps Production - K.N. Afonin; Y.V. Ryapolova; V.S. Soldatkin; V.I. Tuev (Журнал нано- та електронної фізики)
This article presents the results of studies of the effect ultrasonic bonding on the current-voltage characteristic nitrides chips with using methods of planning the experiment.